Isu-isu Kontemporer Filsafat Sosial dalam Perpektif Aliran Eksistensialis: Contemporary Issues in Social Philosophy from an Existentialist Perspective - Feriyansyah, Feriyansyah; Supartiningsih, Supartiningsih (Undiksha, 2024)
This article analyzes contemporary problems in social philosophy from the perspective of existentialism, with the following findings: First, existentialism brings a more comprehensive perspective in understanding social change by placing individual experience and freedom as the starting point. It criticizes established thinking that degrades the subjective dimension and rejects dominating thoughts that simplify human existence as a material object in a social context. Second, existentialism criticizes the construction of social concepts based solely on abstractions and neglects the subjective dimension of humans. It recognizes the importance of emotional, spiritual, and existential dimensions in shaping diverse societies, making existentialism an alternative and comprehensive perspective in analyzing the individual identity process within the context of identity crisis in a modern society limited by norms that restrict individual freedom. Third, existentialism offers alternative solutions to contemporary issues and crises of values in society by placing human experience and uniqueness as the subject in identity formation. It also helps build inclusive and comprehensive views in analyzing contemporary social phenomena.